1991
DOI: 10.2337/diab.40.2.s121
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Prospective Evaluation of Offspring of Diabetic Mothers

Abstract: We have suggested that altered maternal metabolism may affect the subsequent anthropometric and neuropsychological development of children who were in utero during disturbances in maternal fuel economy. This study reports the physical growth through 8 yr of age and the neuropsychological development through 4 yr of age in offspring of diabetic mothers (ODM). At birth, 50% of infants had weights greater than 90th percentile for gestational age. By 12 mo, length and weight were similar to the general population.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
306
7
22

Year Published

1997
1997
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(358 citation statements)
references
References 0 publications
16
306
7
22
Order By: Relevance
“…Nevertheless, analysis of our data by means of BMI as a second independent method, using a different reference population, con®rmed an increase of frequencies of overweight with rising age in infants of diabetic mothers. These observations are in good accordance with those reported by Silverman et al 9 and Gerlini et al 8 Indicating a persistence of increased body weight from birth to later life we observed positive correlations between SI and BMI at birth and SI and BMI in childhood, respectively. Verdy et al 31 reported that overweight newborns of diabetic mothers are at increased risk to be overweight in adulthood too.…”
Section: Children Of Diabetic Mothers a Plagemann Et Alsupporting
confidence: 83%
See 1 more Smart Citation
“…Nevertheless, analysis of our data by means of BMI as a second independent method, using a different reference population, con®rmed an increase of frequencies of overweight with rising age in infants of diabetic mothers. These observations are in good accordance with those reported by Silverman et al 9 and Gerlini et al 8 Indicating a persistence of increased body weight from birth to later life we observed positive correlations between SI and BMI at birth and SI and BMI in childhood, respectively. Verdy et al 31 reported that overweight newborns of diabetic mothers are at increased risk to be overweight in adulthood too.…”
Section: Children Of Diabetic Mothers a Plagemann Et Alsupporting
confidence: 83%
“…A number of investigators used the SI or a variant of this measure to estimate overweight in children. 8,9,15 Weight/height-ratios are known to be good predictors of body fat. 24 In Europe, the use of weight/height-ratio is recommended for estimation of obesity in childhood.…”
Section: Children Of Diabetic Mothers a Plagemann Et Almentioning
confidence: 99%
“…In addition diabetic mothers can give birth to large macrosomic offspring and this intrauterine exposure to diabetes is often a prelude to risk factors M a n u s c r i p t 6 for insulin resistance and type 2 diabetes (18,19). This exposure to maternal diabetes also affects the development of the endocrine pancreas (20) and can manifest itself with elevated levels of insulin in the amniotic fluid during pregnancy (21).…”
Section: Page 5 Of 21mentioning
confidence: 99%
“…Factors that affect birthweight within demographically similar births include pre-pregnancy weight, weight gain during pregnancy, maternal smoking, parity and disease [9]. Maternal diabetes increases birthweight [10,11]. More recently, genes that influence the risk of type 1 diabetes have also been shown to affect birthweight and/or childhood weight gain [12,13].…”
Section: Introductionmentioning
confidence: 99%